Exploring Effective Management of Success Factors for Virtual Teams in the Indian IT industry: A Sales and Marketing Functions’ Case Study - Raskar, Sanket (2015)
he surge in new ways of working through virtual teams has enabled companies to achieve higher productivity levels over the years as they are continually reaping benefits such as the vast reduction in their capex and opex. With the surplus of outsourced technology business in India, virtual teams have found a natural existence in the Information Technology (IT) Industry. The virtual teams however in the IT industry of India have been traditionally associated with Software Engineering, Business process outsourcing, customer services, IT product and services testing and related IT support functions. Over the years as Indian IT professionals gained the required soft skills, an interesting shift has been observed as more IT professionals move towards the business side of the IT industry, specifically towards the functions of IT sales and marketing. Though virtual teams have been studied extensively over the years for their different functionalities, including the Software engineering and other IT services related functions in the Indian IT industry. Virtual teams in the Indian IT industry with IT sales and marketing functions has received little or no attention. Therefore, this research was conducted to explore effective management of success factors for virtual teams in the Indian IT industry with sales and marketing as their core functions. Additional objectives of the research includes identifying the current dynamics or functioning of sales and marketing virtual teams, subsequently identifying the success factors of virtual teams with similar functions that makes them successful, exploring the management strategies that virtual team leaders are incorporating for their teams’ continued higher levels of performance and the issues they face in achieving these performance levels, as well as their future strategies to enhance current performance levels through relevant recommendations. To explore these areas a qualitative approach, of interviewing relevant industry’s virtual team leaders was adopted, wherein 7 virtual team leaders were invited for a discussion to share their insights about their virtual teams. The key findings suggest that team effectiveness is a function of team collaboration through shared mutual understanding, better team integration, cooperative attitudes and competitive conflicts. In accordance to the findings, job effectiveness is influenced indirectly by shared value systems, high levels of perceived trust and perceived benefit, achieved when found collaborating in tandem with cooperative attitude and competitive conflicts. Additionally it is found that Indian IT companies has the potential in terms of right technological infrastructure and required soft skills to expand their market reach by venturing more into virtual teams and developing proficient IT sales and marketing folks and thus consequently aim for higher productivity and profits. The study explores various management styles and strategies leaders use considering their team size and their teams’ lifetime of existence. Finally, this research is aimed at novel exploration of this topic in order to educate future virtual team leaders of similar functions and provide a theory for global supply chain managers to understand ways to make their global supply chains competitive.